A waste plastic conversion catalyst and a method for preparing the same

CN118179575BActive Publication Date: 2026-10-09CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211575691.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-09
Publication Date
2026-10-09
Estimated Expiration
2042-12-09

AI Technical Summary

Technical Problem

这些方式可以利用现有装置,操作的灵活性高,可满足不同的产品需求,但需要不同的工艺耦合,工艺过程复杂,经济性差

Benefits of technology

1、本发明提供的废塑料转化催化剂具有裂解和加氢两种活性中心,在对废塑料处理时可以在裂解的同时对生成的小分子烃类化合物进行加氢,保证得到优质的乙烯料产品。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a waste plastic conversion catalyst and a preparation method thereof. The waste plastic conversion catalyst comprises a silicon-aluminum compound containing a modified molecular sieve and a first active metal component supported thereon, and the modified molecular sieve is a molecular sieve loaded with a second active metal component. The preparation method comprises the following steps: (1) preparing a silicon-aluminum composite sol; (2) preparing a pretreated molecular sieve; (3) mixing the pretreated molecular sieve obtained in the step (2) with the silicon-aluminum composite sol obtained in the step (1) to perform a reaction, and then performing aging and drying treatment to obtain a catalyst precursor; and (4) introducing an active component to the catalyst precursor, and then performing shaping, drying and calcination to obtain the catalyst. The catalyst has the advantages of high activity, good selectivity and the like when treating waste plastics, and the preparation method is simple and economical.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalytic materials technology, and in particular relates to a waste plastic conversion catalyst and its preparation method. Background Technology

[0002] Plastics are widely used in all aspects of society due to their excellent durability, corrosion resistance, plasticity, and stability. Their production and consumption have become important indicators for assessing industrial development and people's quality of life. Since large-scale production began, global plastic production has steadily increased year by year, reaching 359 million tons in 2018, with an annual growth rate of approximately 3.2%. One of the biggest problems we face is the pollution caused by plastics, and the most effective way to reduce plastic pollution is to increase the recycling rate of waste plastics and enhance their resource utilization value.

[0003] Waste plastics can be transformed into high-quality chemical raw materials through physicochemical recycling and thermochemical utilization, thus achieving clean and efficient recycling of waste plastics. Compared with traditional recycling methods, pyrolysis is a relatively environmentally friendly, economically feasible technology with promising prospects for large-scale industrial application. Currently, pyrolysis mainly includes four methods: thermal cracking, catalytic cracking, pyrolysis-catalytic modification, and catalytic cracking-catalytic modification. Thermal cracking has a high reaction temperature and long reaction time, resulting in low yield and quality of the liquid oil product; catalytic cracking catalysts are easily deactivated and difficult to separate, so current research mainly focuses on two processes: pyrolysis-catalytic modification and catalytic cracking-catalytic modification. Both of these processes require at least two processes to be completed in tandem. Waste plastics are first cracked to generate cracked oil, which is then modified to obtain the target product. However, many problems still need to be solved, such as poor quality of finished oil, many by-products, high energy consumption, and high catalyst consumption.

[0004] CN202010001451.2 discloses a method for recycling waste plastics. Waste plastics are heated and melted in a furnace, then injected into a coking tower for delayed coking to obtain high-temperature oil and gas and coke. The high-temperature oil and gas are filtered and then separated in a fractionation tower to obtain coking dry gas and coking distillate. The coking distillate enters a riser for catalytic cracking, and the resulting oil and gas products are separated in a fractionation tower after passing through a settling tank to obtain catalytic rich gas, gasoline, diesel, and recycled oil. The coking dry gas and catalytic rich gas are sent to a gas separation unit to be separated into dry gas and liquefied petroleum gas (LPG). The catalytic gasoline and diesel can be used as blending components or further refined. The recycled oil is transported to a riser reactor for reprocessing or used as an external discharge device for oil slurry components. This method for recycling waste plastics has the following advantages: high oil and gas yield, wide product selection flexibility, and the ability to produce high-value-added LPG, gasoline, and diesel, resulting in high economic benefits. CN202010903085.X discloses a method and system for processing waste plastics. The method involves introducing waste plastics into a fluidized bed reactor, where they contact a pretreatment catalyst and undergo a catalytic decomposition reaction. The reaction products are separated to obtain plastic-derived oil, and the spent pretreatment catalyst is recycled after coking. The plastic-derived oil is then contacted with a catalytic conversion catalyst for a catalytic conversion reaction. The reaction oil and gas are separated from the spent catalytic conversion catalyst, yielding a product containing propylene. This spent catalytic conversion catalyst is also recycled after coking. This invention converts waste plastics into high-value products such as low-carbon olefins, reducing environmental pollution and achieving high-value utilization of waste plastics while reducing resource consumption. While these methods can utilize existing equipment, offer high operational flexibility, and meet diverse product needs, they require different process couplings, resulting in complex processes and poor economic efficiency. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a waste plastic conversion catalyst and its preparation method. The prepared catalyst contains both a metal active phase suitable for hydrogenation and a cracking component, exhibiting advantages such as high activity and good selectivity in the treatment of waste plastics. Moreover, the preparation method is simple and economical.

[0006] To achieve the above-mentioned objective, the present invention first provides a waste plastic conversion catalyst, which comprises a silicon-aluminum compound containing a modified molecular sieve and a first active metal component supported thereon. The modified molecular sieve is a molecular sieve supported with a second active metal component. The first active metal component is one or more of Group VIB metals and Group VIII metals. The second active metal component is molybdenum and nickel. Both the first and second active metal components exist in a sulfide state. Based on the weight of the catalyst, the total content of the first and second active metal components, calculated as oxides, is 5wt% to 35wt%.

[0007] Furthermore, in the above-mentioned waste plastic conversion catalyst, as a preferred embodiment, the silicon-aluminum compound containing modified molecular sieve accounts for 65% to 95% by weight.

[0008] Furthermore, in the above-mentioned waste plastic conversion catalyst, as a preferred embodiment, the waste plastic conversion catalyst includes two-stage channels, wherein the pore size of the first-stage channel is 0.5-10 nm and the pore size of the second-stage channel is 20-100 nm.

[0009] Furthermore, in the above-mentioned waste plastic conversion catalyst, as a preferred embodiment, the silicon-aluminum compound is alumina with a silicon content (calculated as silicon dioxide) of 3wt% to 40wt%, preferably with a silicon content of 5wt% to 35wt%.

[0010] Furthermore, in the above-mentioned waste plastic conversion catalyst, as a preferred embodiment, the molecular sieve is a molecular sieve with acidic centers, such as at least one of Y, ZSM-5, β, MOR, MCM-41, and MCM-22 molecular sieves, preferably a modified molecular sieve, specifically one or more of HY, REY, USY, REHY, REUSY, and HZSM-5 molecular sieves.

[0011] In another aspect, the present invention provides a method for preparing a waste plastic conversion catalyst, the method comprising the following steps: (1) The silica sol aqueous solution and the aluminum sol precursor were mixed and hydrolyzed to obtain a silica-alumina composite sol; (2) Mix the organic nickel salt, organic molybdenum and hydrocarbon compounds, then introduce them into the molecular sieve for impregnation treatment, and then obtain the pretreated molecular sieve after further separation and heat treatment; (3) The pretreated molecular sieve obtained in step (2) is mixed with the silica-alumina composite sol obtained in step (1) and reacted, and then further aged and dried to obtain the catalyst precursor; (4) The catalyst is obtained by mixing the catalyst precursor obtained in step (3), the compound containing Group VIII metal, the sulfide precursor containing Group VIB metal, the peptide solvent and the extrusion aid, and then molding, drying and calcining.

[0012] In the above-mentioned method for preparing the waste plastic conversion catalyst, as a preferred embodiment, the aluminum sol precursor in step (1) can be an organic aluminum-containing compound and / or an inorganic aluminum-containing compound; wherein, the organic aluminum-containing compound can be selected from one or more of alkyl aluminum and alkoxy aluminum; furthermore, the alkyl aluminum can be at least one of trimethyl aluminum, triethyl aluminum, tripropyl aluminum, and triisobutyl aluminum, and the alkoxy aluminum has 3 to 20 carbon atoms, specifically selected from at least one of triethanolamine aluminum, tripropoxide aluminum, triisopropoxide aluminum, and tri-n-butoxy aluminum; when using an organic aluminum-containing compound as the aluminum sol precursor, it is preferred to mix the organic aluminum-containing compound with ethanol to obtain an aluminum sol prepreg, and the weight ratio of the organic aluminum-containing compound to ethanol is 5:1 to 1:10. The inorganic aluminum-containing compound can be selected from one or more of aluminum sulfate, aluminum nitrate, aluminum chloride, and sodium aluminate.

[0013] In the above-mentioned method for preparing the waste plastic conversion catalyst, as a preferred embodiment, the silica sol in step (1) contains 1wt% to 50wt% silica, preferably 5wt% to 35wt% silica; the sodium oxide content is less than 0.1wt%, preferably less than 0.05wt% silica; the silica sol can be prepared in-house or according to methods disclosed in the prior art, or it can be purchased as a commercial product. The silica sol can be prepared by hydrolysis of a silicon source, and the silicon source can be selected from one or more of water glass, sodium silicate, and tetraethylsilane aqueous solution.

[0014] In the above-mentioned method for preparing the waste plastic conversion catalyst, as a preferred embodiment, the hydrolysis reaction in step (1) can be carried out under acidic (pH 5-7) or alkaline (pH 7-9) conditions. Generally, the acidic or alkaline conditions are adjusted by adding acidic or alkaline substances. The acidic substances used can be one or more of inorganic acids and organic acids. Specifically, the acidic substances can be selected from one or more of nitric acid, sulfuric acid, hydrochloric acid, acetic acid, formic acid, and carbonic acid. The alkaline substances used are selected from one or more of sodium hydroxide, potassium hydroxide, ammonia, and sodium aluminate.

[0015] In the above-mentioned method for preparing waste plastic conversion catalyst, as a preferred embodiment, the organic nickel salt in step (2) can be selected from one or more of nickel formate, nickel propionate, nickel butyrate, nickel octanoate, nickel lactate, nickel benzoate, nickel acetylacetone, bis(hexafluoroacetylacetone) nickel(II), bis(1,5-cyclooctadiene) nickel, nickel salicylate, nickel naphthenate, nickel 2-ethylhexanoate, nickel citrate, etc.; preferably one or more of nickel formate, nickel acetylacetone, and nickel citrate.

[0016] In the above-mentioned method for preparing waste plastic conversion catalyst, as a preferred embodiment, the organic molybdenum is one or more of hydrocarbon-based molybdenum thiophosphate, molybdenum naphthenate, and molybdenum alkyl salicylate. The hydrocarbon group in the hydrocarbon-based molybdenum thiophosphate is a substituent with fewer than 20 carbon atoms and can be at least one of alkanes, alkenes, and aromatics. More specifically, the organic molybdenum can be one or more of dialkyl dithiophosphate, dialkyl dithiocarbamate, and diisopropyl dithiophosphate sulfide.

[0017] In the above-mentioned method for preparing waste plastic conversion catalyst, as a preferred embodiment, the hydrocarbon compound is a hydrocarbon with 4 to 30 carbon atoms, which can be alkanes, cycloalkanes, aromatics, or other hydrocarbon substances, or it can be an element or compound of the corresponding hydrocarbon such as alcohols, aldehydes, acids, etc., such as one or more of gasoline, kerosene, diesel, wax oil, palm oil, soybean oil, ethanol, glycerol, ethylene glycol, formaldehyde, and fatty acids.

[0018] In the above-mentioned method for preparing waste plastic conversion catalyst, as a preferred embodiment, the impregnation treatment of molecular sieve in step (2) can be saturated impregnation or supersaturated impregnation. After the molecular sieve is drained of hydrocarbon substances, it is subjected to low-temperature heat treatment. The heat treatment conditions are adjusted according to the type of hydrocarbon compound used. The heat treatment temperature is generally 50 to 180°C and the heat treatment time is generally 2 to 12 hours.

[0019] In the above-mentioned method for preparing waste plastic conversion catalyst, as a preferred embodiment, the molecular sieve is a molecular sieve with acidic centers, such as at least one of Y, ZSM-5, β, MOR, MCM-41, and MCM-22 molecular sieves, preferably a modified molecular sieve. This invention does not particularly limit the specific modification method; those skilled in the art can make appropriate selections according to specific circumstances. Specifically, it can be one or more of HY, REY, USY, REHY, REUSY, and HZSM-5 molecular sieves.

[0020] In the above-mentioned method for preparing waste plastic conversion catalyst, as a preferred embodiment, the separation in step (2) can be achieved by any of the liquid-solid two-phase separation methods in the art, such as filtration separation, centrifugal separation, etc.

[0021] In the above-mentioned method for preparing waste plastic conversion catalyst, as a preferred embodiment, the reaction temperature in step (3) is 40℃~80℃.

[0022] In the above-mentioned method for preparing waste plastic conversion catalyst, as a preferred embodiment, the aging time in step (3) is 2 to 12 hours.

[0023] In the above-mentioned method for preparing waste plastic conversion catalyst, as a preferred embodiment, the drying in step (3) is carried out under supercritical conditions. Furthermore, the drying medium for supercritical drying is carbon dioxide, the pressure is 1-15 MPa, the drying temperature is 20-100℃, and the flow rate of the drying medium is 40 liters / hour to 500 liters / hour.

[0024] In the above-mentioned method for preparing waste plastic conversion catalyst, as a preferred embodiment, the VIB group metal in step (4) is preferably Mo and / or W, and the VIB group metal sulfide precursor can be thiomolybdate and / or thiotungstate, more preferably ammonium salt. More specifically, the thiomolybdate can be any one or more of tetrathiomolybdate and hydrocarbon thiomolybdate; the thiotungstate can be any one or more of tetrathiotungstate and hydrocarbon thiotungstate; the number of hydrocarbon carbon atoms in hydrocarbon thiomolybdate and hydrocarbon thiotungstate is generally 1 to 80, preferably 2 to 20; it can be a saturated hydrocarbon group or an unsaturated hydrocarbon group, such as alkyl, cycloalkyl, olefin, etc.

[0025] In the above-mentioned method for preparing waste plastic conversion catalyst, as a preferred embodiment, the compound containing group VIII metal in step (4) can be an inorganic salt containing group VIII metal or a complex containing group VIII metal, and the group VIII metal is preferably Ni and / or Co; further, more specifically, the compound containing group VIII metal can be selected from one or more of nickel nitrate, basic nickel carbonate, nickel citrate, cobalt nitrate, basic cobalt carbonate, and cobalt citrate.

[0026] In the above-mentioned method for preparing waste plastic conversion catalyst, as a preferred embodiment, the extrusion aid and adhesive solvent in step (4) are well known to those skilled in the art, and the specific types and amounts of substances used can be determined according to existing knowledge in the art. Preferably, the extrusion aid can be one or more of guar gum powder, starch, methylcellulose, polyvinyl alcohol, and polyethylene glycol, and its amount is 1.0wt% to 5.0wt% of the catalyst weight. The adhesive solvent is one or more of nitric acid, oxalic acid, and phosphoric acid, and its amount is 1.0wt% to 10.0wt% of the catalyst weight.

[0027] In the above-mentioned method for preparing waste plastic conversion catalyst, as a preferred embodiment, the drying temperature in step (4) is 50-180℃, preferably 80-150℃, and the drying time is 1-24h, preferably 3-12h.

[0028] In the above-mentioned method for preparing waste plastic conversion catalyst, as a preferred embodiment, the calcination in step (4) is carried out in an inert atmosphere, which is any one of nitrogen and / or inert gas; the calcination temperature is 400℃~770℃, preferably 450℃~650℃; the calcination time is 1~12h, preferably 3~8h.

[0029] A third aspect of the present invention provides a waste plastic conversion catalyst obtained by the above preparation method.

[0030] The fourth aspect of the present invention provides a waste plastic treatment method, wherein the waste plastic is treated in the presence of the above-mentioned waste plastic conversion catalyst or the waste plastic conversion catalyst obtained by the above preparation method, and high-quality ethylene feedstock is obtained after treatment.

[0031] In the above-mentioned waste plastic treatment method, as a preferred embodiment, the waste plastic is polyolefin waste plastic.

[0032] In the above-mentioned waste plastic treatment methods, as a preferred embodiment, the treatment conditions are generally: reaction temperature of 380-450℃ and reaction pressure of 2.0-8.0MPa.

[0033] Compared with the prior art, the waste plastic conversion catalyst and its preparation method provided by the present invention have the following technical effects: 1. The waste plastic conversion catalyst provided by this invention has two active centers: cracking and hydrogenation. When treating waste plastics, it can hydrogenate the generated small molecule hydrocarbon compounds at the same time as cracking, ensuring that high-quality ethylene products are obtained.

[0034] 2. The waste plastic conversion catalyst provided by this invention contains an aerogel composite of molecular sieves. The aerogel has large pores and high porosity, which facilitates the entry of large molecular weight plastic raw materials. Waste plastics are decomposed into smaller molecules within the aerogel pores and then enter the molecular sieve pores for further pyrolysis. Simultaneously, hydrogenation occurs at the metal active sites, ultimately generating the target product. This solves the problem that waste plastics, being large polymer molecules with large molecular weights and long carbon chains, cannot directly enter the conventional molecular sieve pores to react in acidic centers, thus affecting the pyrolysis activity of the molecular sieves.

[0035] 3. In the preparation method of waste plastic conversion catalyst provided by the present invention, the molecular sieve is modified and pretreated to have a non-polar protective film on the surface of the molecular sieve, which ensures the uniform dispersion and stability of the molecular sieve in the sol and gel. Moreover, the presence of hydrocarbon substances in the molecular sieve channels also prevents sol molecules from entering the molecular sieve channels, ensuring that the formed silicon-aluminum composite is a network structure of silicon-aluminum aerogel, with molecular sieves distributed and dotting it to form several islands. After subsequent calcination, the channels of the molecular sieve are restored.

[0036] 4. This invention can obtain the target product using a single catalyst, and the supporting process is simple and highly economical. Detailed Implementation

[0037] The technical features of the present invention are further described below through embodiments, but these embodiments are not intended to limit the present invention.

[0038] Unless otherwise specified, the pore size in this paper was measured using the cryogenic liquid nitrogen physical adsorption method, and the instrument used was the ASAP2405 / 2420 physical adsorption instrument manufactured by the American company.

[0039] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0040] All chemical reagents used in this article are commercially available and can be purchased. The pore size of Y molecular sieve is 2.15 nm, that of MCM-41 molecular sieve is 5.72 nm, and that of ZSM-5 molecular sieve is 0.55 nm.

[0041] Example 1 Aluminum isopropoxide and ethanol were mixed in a 5:1 ratio and added to a commercially available silica gel solution (containing 8 wt% silica particles at 25 nm). The pH was maintained at 7.5, and hydrolysis was carried out at room temperature (25°C) for 2 hours. The weight ratio of alumina to silica in the sol was 80:20. 3 g of copper-nickel acetate and 20 g of molybdenum dialkyl dithiophosphate were added to a hydrocarbon mixture (glycerol: gasoline weight ratio of 1:5) to form a pretreatment solution. 7.5 g of Y molecular sieve powder was saturated and impregnated for 2 hours, then treated in a 60°C forced-air drying oven for 3 hours. The treated molecular sieve was added to the sol, making it account for 15 wt% of the aerosol. The mixture was stirred evenly and then transferred to a 50°C constant-temperature water bath for 3 hours to form a silica-alumina gel. Supercritical drying was then carried out in a carbon dioxide system at a drying pressure of 4 MPa, a drying temperature of 50°C, and a carbon dioxide flow rate of 100 L / h to obtain the catalyst precursor.

[0042] The catalyst precursor was mixed with nickel nitrate solution (containing 16 wt% nickel oxide), ammonium thiomolybdate solution (containing 30 wt% molybdenum oxide), nitric acid, and guar gum powder. The mixture was kneaded and extruded into strips, dried at 150°C for 5 hours under nitrogen protection, and calcined at 550°C for 3 hours to obtain the finished catalyst. The composition and properties of the catalyst are shown in Table 1.

[0043] Example 2 A mixture of 2 mol / L aluminum nitrate and silica gel solution (25 wt% silica, 20 nm silica particles) was prepared, and ammonia was added to adjust the pH to 6.5. The mixture was reacted at 60°C for 1 hour, resulting in an alumina to silica weight ratio of 75:25 in the sol. 6 g of nickel citrate and 25 g of molybdenum dialkyldithiocarbamate were added to a hydrocarbon mixture (ethanol:palm oil weight ratio 1:3) to form a pretreatment solution. 9 g of ZSM-5 molecular sieve powder was saturated and impregnated for 1 hour, then dried in a 70°C oven for 3 hours. The treated molecular sieve was added to the sol, making it 18 wt% of the aerosol, and stirred thoroughly. The mixture was then aged in a 60°C constant temperature water bath for 4 hours to form a silica-alumina gel. The gel was then subjected to supercritical drying in a carbon dioxide system at a pressure of 6 MPa, a temperature of 60°C, and a carbon dioxide flow rate of 150 L / h to obtain the catalyst precursor.

[0044] The catalyst precursor was mixed with nickel nitrate solution (containing 20 wt% nickel oxide), ammonium thiomolybdate solution (containing 35 wt% molybdenum oxide), nitric acid, and polyvinyl alcohol. The mixture was kneaded and extruded into strips, dried at 150°C for 5 hours under nitrogen, and calcined at 550°C for 3 hours to obtain the finished catalyst. The composition and properties of the catalyst are shown in Table 1.

[0045] Example 3 Aluminum sulfate solution was added to a commercially available silica gel solution containing 30% silica particles of 15 nm. Ammonia was slowly added dropwise at 65°C to adjust the pH to 7.5, resulting in an alumina to silica weight ratio of 85:15 in the sol. 2.1 g of nickel acetate and 28 g of molybdenum diisopropyl dithiophosphate sulfide were added to a hydrocarbon mixture (soybean oil: n-heptane = 1:1) to form a pretreatment solution. 5 g of MCM-41 molecular sieve powder was saturated in the pretreatment solution for 3 hours and then treated in a 100°C forced-air drying oven for 4 hours. The treated molecular sieve was added to the sol, ensuring it comprised 10% of the aerosol. The mixture was stirred thoroughly and then aged in a 70°C constant-temperature water bath for 5 hours to form a silica-alumina gel. The gel was then subjected to supercritical drying in a carbon dioxide system under the same conditions as in Example 1 to obtain the catalyst precursor.

[0046] The catalyst precursor was mixed with nickel nitrate solution (containing 12 wt% nickel oxide), ammonium thiomolybdate solution (containing 20 wt% molybdenum oxide), nitric acid, and guar gum powder. The mixture was kneaded and extruded into strips, dried at 150°C for 5 hours under nitrogen, and calcined at 600°C for 3 hours to obtain the finished catalyst. The composition and properties of the catalyst are shown in Table 1.

[0047] Example 4 Tetraethyl orthosilicate was diluted with water to a SiO2 concentration of 30 wt%, hydrolyzed at 65°C, and aged at this temperature for 2 hours. A 10% acetic acid solution was added dropwise until the pH reached 5.5. Then, aluminum chloride solution was slowly added under stirring, and ammonia was added to adjust the pH to 7. The weight ratio of alumina to silica in the sol was 85:15. 10 g of MCM-41 molecular sieve powder was added, with the molecular sieve pretreatment being the same as in Example 1, ensuring it comprised 20 wt% of the aerosol. The mixture was then aged at 70°C for 4.5 hours to form an aluminosilicate gel. The gel was then subjected to supercritical drying in a carbon dioxide system at a pressure of 3 MPa, a temperature of 75°C, and a carbon dioxide flow rate of 200 L / h. This yielded the catalyst precursor.

[0048] The catalyst precursor was mixed with ammonium thiotungstate (20 wt% tungsten oxide), ammonium thiomolybdate (15 wt% molybdenum oxide), cobalt nitrate solution (3.5 wt% cobalt oxide), nitric acid, and guar gum powder. The mixture was kneaded and extruded into strips, dried at 160°C for 3 hours under nitrogen atmosphere, and calcined at 600°C for 3 hours to obtain the finished catalyst. The composition and properties of the catalyst are shown in Table 1.

[0049] Comparative Example 1 Amorphous silica-alumina (pore size 17nm), SB powder and Y molecular sieve were mixed evenly in a ratio of 75:10:15, and then mixed with ammonium thiomolybdate solution (molybdenum oxide concentration of 35wt%), nickel nitrate solution (containing nickel oxide of 16wt%), guar gum powder and dilute nitric acid and extruded into strips. The mixture was dried at 150℃ for 5 hours under nitrogen and calcined at 500℃ for 3 hours to obtain the final product catalyst. The composition and properties of the catalyst are shown in Table 1.

[0050] Comparative Example 2 Aluminum isopropoxide and ethanol were mixed in a 5:1 ratio and added to a commercially available silica gel solution (containing 8 wt% silica particles at 25 nm). The pH was maintained at 7.5, and hydrolysis was performed at room temperature for 2 hours. The alumina to silica weight ratio in the sol was 80:20. 7.5 g of Y molecular sieve powder was added to the sol, making it 15 wt% of the aerosol. The mixture was stirred thoroughly and then transferred to a 50°C constant temperature water bath and allowed to stand for 3 hours to form an aluminosilicate gel. The gel was aged for 2 hours and then subjected to supercritical drying in a carbon dioxide system at a pressure of 4 MPa, a temperature of 50°C, and a carbon dioxide flow rate of 100 L / h to obtain the catalyst precursor.

[0051] The catalyst precursor was mixed with nickel nitrate solution (containing 18 wt% nickel oxide), ammonium thiomolybdate solution (containing 35 wt% molybdenum oxide), nitric acid, and guar gum powder. The mixture was kneaded and extruded into strips, dried at 150°C for 5 hours under nitrogen protection, and calcined at 550°C for 3 hours to obtain the finished catalyst. The composition and properties of the catalyst are shown in Table 1.

[0052] Evaluation Test Methods for evaluating the activity of catalysts prepared in Examples 1-4 and Comparative Examples 1-2: The catalyst and waste PP plastic were loaded into a high-pressure reactor. The hydrogen gas was sealed and heated to 370°C at a rate of 20°C / h. The reactor was stirred while heating at a pressure of 6 MPa. After holding the temperature for 0.5 hours, the temperature was lowered. After cooling to room temperature, the gas from the apparatus was collected for analysis. The collected liquid was then analyzed after opening the high-pressure reactor. The evaluation results are shown in Table 2.

[0053] Table 1. Physicochemical properties and evaluation results of the catalysts Table 2 Results of waste plastic conversion Table 3 Composition distribution of liquids at <350℃ As shown in Tables 1 and 2, the waste plastic conversion catalyst prepared by this technology possesses bimodal channels and large pore sizes of silicon-aluminum compounds, which is beneficial for polymer adsorption and reaction. After the polymer is decomposed into smaller fragments, it enters the molecular sieve channels for further pyrolysis into smaller molecules, while simultaneously undergoing hydrogenation. This results in a high conversion rate of waste plastics, a high proportion of gas, coal, and diesel in the product, and less pyrolysis gas generation, thus improving the utilization rate of waste plastics. The low pyrolysis activity in Comparative Example 2 is due to the agglomeration of the molecular sieve in the sol and the entry of sol particles into the molecular sieve channels, ultimately clogging the channels and covering the acidic centers of the molecular sieve, leading to decreased activity. Table 3 lists the composition distribution results of the liquid at <350℃. As shown in Table 3, the product obtained in the example has a high content of saturated hydrocarbons, making it a high-quality ethylene cracking feedstock.

Claims

1. A catalyst for the conversion of waste plastics, characterized in that: The waste plastic conversion catalyst comprises a silica-alumina compound containing a modified molecular sieve and a first active metal component supported thereon. The modified molecular sieve is a molecular sieve supported with a second active metal component. The first active metal component is one or more of Group VIB and Group VIII metals. The second active metal component is molybdenum and nickel. Both the first and second active metal components exist in a sulfide state. The waste plastic conversion catalyst comprises two-stage channels, wherein the pore size of the first-stage channels is 0.5–10 nm, and the pore size of the second-stage channels is 20–100 nm. The preparation method of the waste plastic conversion catalyst includes the following steps: (1) The silica sol aqueous solution and the aluminum sol precursor were mixed and hydrolyzed to obtain a silica-alumina composite sol; (2) Mix the organonitrile salt, organomolybdenum and compound A, then introduce them into the molecular sieve for impregnation treatment, and then obtain the pretreated molecular sieve after further separation and heat treatment; compound A is one or more of glycerol, gasoline, ethanol, palm oil and soybean oil; (3) The pretreated molecular sieve obtained in step (2) is mixed with the silica-alumina composite sol obtained in step (1) and reacted, and then further aged and dried to obtain the catalyst precursor; (4) The catalyst is obtained by mixing the catalyst precursor obtained in step (3), the compound containing Group VIII metal, the sulfide precursor containing Group VIB metal, the peptide solvent and the extrusion aid, and then molding, drying and calcining.

2. The waste plastic conversion catalyst according to claim 1, characterized in that: Based on the weight of the catalyst, the total content of the first active metal component and the second active metal component, calculated as oxides, is 5wt% to 35wt%.

3. The waste plastic conversion catalyst according to claim 1, characterized in that: The weight proportion of silicon-aluminum compounds in silicon-aluminum compounds containing modified molecular sieves is 65% to 95%.

4. The waste plastic conversion catalyst according to claim 1, characterized in that: The molecular sieve is at least one of Y, ZSM-5, β, MOR, MCM-41, and MCM-22 molecular sieves.

5. A method for preparing a waste plastic conversion catalyst, the method comprising the following steps: (1) The silica sol aqueous solution and the aluminum sol precursor were mixed and hydrolyzed to obtain a silica-alumina composite sol; (2) Mix the organonitrile salt, organomolybdenum and compound A, then introduce them into the molecular sieve for impregnation treatment, and then obtain the pretreated molecular sieve after further separation and heat treatment; compound A is one or more of glycerol, gasoline, ethanol, palm oil and soybean oil; (3) The pretreated molecular sieve obtained in step (2) is mixed with the silica-alumina composite sol obtained in step (1) and reacted, and then further aged and dried to obtain the catalyst precursor; (4) The catalyst is obtained by mixing the catalyst precursor obtained in step (3), the compound containing Group VIII metal, the sulfide precursor containing Group VIB metal, the peptide solvent and the extrusion aid, and then molding, drying and calcining.

6. A method for preparing a waste plastic conversion catalyst, the preparation method comprising the following steps: (1) The silica sol aqueous solution and the aluminum sol precursor were mixed and hydrolyzed to obtain a silica-alumina composite sol; (2) Mix the organonitrile salt, organomolybdenum and compound A, then introduce them into the molecular sieve for impregnation treatment, and then obtain the pretreated molecular sieve after further separation and heat treatment; compound A is a mixture of soybean oil and n-heptane; (3) The pretreated molecular sieve obtained in step (2) is mixed with the silica-alumina composite sol obtained in step (1) and reacted, and then further aged and dried to obtain the catalyst precursor; (4) The catalyst is obtained by mixing the catalyst precursor obtained in step (3), the compound containing Group VIII metal, the sulfide precursor containing Group VIB metal, the peptide solvent and the extrusion aid, and then molding, drying and calcining.

7. The method for preparing the waste plastic conversion catalyst according to claim 5 or 6, characterized in that: In step (1), the aluminum sol precursor is an organic aluminum-containing compound and / or an inorganic aluminum-containing compound; wherein, the organic aluminum-containing compound is selected from one or more of alkyl aluminum and alkoxy aluminum; the alkyl aluminum is at least one of trimethyl aluminum, triethyl aluminum, tripropyl aluminum, and triisobutyl aluminum; the alkoxy aluminum has 3 to 20 carbon atoms and is selected from at least one of triethanolaluminum, tripropoxide aluminum, triisopropoxide aluminum, and tri-n-butoxy aluminum; the inorganic aluminum-containing compound is selected from one or more of aluminum sulfate, aluminum nitrate, aluminum chloride, and sodium aluminate.

8. The method for preparing the waste plastic conversion catalyst according to claim 7, characterized in that: When using an organic aluminum compound as an aluminum sol precursor, the organic aluminum compound is mixed with ethanol to obtain an aluminum sol prepreg, and the weight ratio of the organic aluminum compound to ethanol is 5:1 to 1:

10.

9. The method for preparing the waste plastic conversion catalyst according to claim 5 or 6, characterized in that: The silica content in the silica sol in step (1) is 1wt% to 50wt%.

10. The method for preparing the waste plastic conversion catalyst according to claim 5 or 6, characterized in that: The silica content in the silica sol in step (1) is 5wt% to 35wt%.

11. The method for preparing the waste plastic conversion catalyst according to claim 5 or 6, characterized in that: The organic nickel salt in step (2) is selected from one or more of nickel formate, nickel propionate, nickel butyrate, nickel octanoate, nickel lactate, nickel benzoate, nickel acetylacetone, bis(hexafluoroacetylacetone) nickel, bis(1,5-cyclooctadiene) nickel, nickel salicylate, nickel naphthenate, nickel 2-ethylhexanoate, and nickel citrate.

12. The method for preparing the waste plastic conversion catalyst according to claim 5 or 6, characterized in that: The organic nickel salt in step (2) is selected from one or more of nickel formate, nickel acetylacetonate, and nickel citrate.

13. The method for preparing the waste plastic conversion catalyst according to claim 5 or 6, characterized in that: Organic molybdenum is one or more of alkyl thiophosphate molybdenum, naphthenic molybdenum, and alkyl salicylic acid molybdenum. Among them, the alkyl group in alkyl thiophosphate molybdenum is a substituent with fewer than 20 carbon atoms and is at least one of alkanes, alkenes, and aromatics.

14. The method for preparing the waste plastic conversion catalyst according to claim 5 or 6, characterized in that: Organic molybdenum is one or more of dialkyl dithiophosphate molybdenum oxide, dialkyl dithiocarbamate molybdenum oxide, and diisopropyl dithiophosphate molybdenum sulfide.

15. The method for preparing the waste plastic conversion catalyst according to claim 5 or 6, characterized in that: The heat treatment temperature in step (2) is 50 to 180°C, and the heat treatment time is 2 to 12 hours.

16. The method for preparing the waste plastic conversion catalyst according to claim 5 or 6, characterized in that: The molecular sieve is at least one of Y, ZSM-5, β, MOR, MCM-41, and MCM-22 molecular sieves.

17. The method for preparing the waste plastic conversion catalyst according to claim 5 or 6, characterized in that: The reaction temperature in step (3) is 40℃~80℃; the aging time is 2~12 hours.

18. The method for preparing the waste plastic conversion catalyst according to claim 5 or 6, characterized in that: In step (3), the drying is carried out under supercritical conditions. The drying medium for supercritical drying is carbon dioxide, the pressure is 1-15 MPa, and the drying temperature is 20-100℃.

19. The method for preparing the waste plastic conversion catalyst according to claim 5 or 6, characterized in that: In step (4), the Group VIB metal is Mo and / or W, and the sulfide precursor containing the Group VIB metal is thiomolybdate and / or thiotungstate. The thiomolybdate is any one or more of tetrathiomolybdate and hydrocarbon thiomolybdate; the thiotungstate is any one or more of tetrathiotungstate and hydrocarbon thiotungstate; the number of hydrocarbon carbon atoms in the hydrocarbon thiomolybdate and hydrocarbon thiotungstate is 1 to 80.

20. The method for preparing the waste plastic conversion catalyst according to claim 19, characterized in that: The number of hydrocarbon carbon atoms in hydrocarbon thiomolybdates and hydrocarbon thiotungstates ranges from 2 to 20.

21. The method for preparing the waste plastic conversion catalyst according to claim 5 or 6, characterized in that: The compound containing Group VIII metal in step (4) is an inorganic salt containing Group VIII metal or a complex containing Group VIII metal, wherein the Group VIII metal is Ni and / or Co.

22. The method for preparing the waste plastic conversion catalyst according to claim 5 or 6, characterized in that: The compound containing group VIII metals in step (4) is selected from one or more of nickel nitrate, basic nickel carbonate, nickel citrate, cobalt nitrate, basic cobalt carbonate, and cobalt citrate.

23. The method for preparing the waste plastic conversion catalyst according to claim 5 or 6, characterized in that: The extrusion aid in step (4) is one or more of the following: guar gum powder, starch, methylcellulose, polyvinyl alcohol, and polyethylene glycol; the adhesive solvent is one or more of the following: nitric acid, oxalic acid, and phosphoric acid.

24. The method for preparing the waste plastic conversion catalyst according to claim 5 or 6, characterized in that: In step (4), the drying temperature is 50-180℃ and the drying time is 1-24h.

25. The method for preparing the waste plastic conversion catalyst according to claim 5 or 6, characterized in that: In step (4), the drying temperature is 80-150℃ and the drying time is 3-12h.

26. The method for preparing the waste plastic conversion catalyst according to claim 5 or 6, characterized in that: The calcination described in step (4) is carried out in an inert atmosphere, which is any one of nitrogen and / or inert gas; the calcination temperature is 400℃~770℃, and the calcination time is 1~12h.

27. The method for preparing the waste plastic conversion catalyst according to claim 5 or 6, characterized in that: The calcination described in step (4) is carried out in an inert atmosphere, which is any one of nitrogen and / or inert gas; the calcination temperature is 450℃~650℃, and the calcination time is 3~8h.

28. A method for treating waste plastics, wherein the waste plastics are treated in the presence of the waste plastic conversion catalyst described in any one of claims 1-4 or the waste plastic conversion catalyst obtained by the preparation method described in any one of claims 5-27.

29. The waste plastic treatment method according to claim 28, characterized in that: The waste plastics are polyolefin waste plastics.

30. The waste plastic treatment method according to claim 28, characterized in that: The reaction temperature is 380–450℃, and the reaction pressure is 2.0–8.0 MPa.

Citation Information

Patent Citations

  • Waste plastic recycling method

    CN111057569A

  • Processing method and system of waste plastics

    CN114106865A

  • Hydrocracking catalyst preparation method

    CN106944125A